Pelos caminhos das águas: a mobilidade e evolução da COVID-19 no estado do Amazonas - Natacha Cíntia Regina Aleixo; João Cândido André da Silva Neto; Henrique dos Santos Pereira; Danilo Egle Santos Barbosa; Bruno Cordeiro Lorenzi (Confins)
The objective of the research was to analyse the mobility and evolution of COVID-19 in the state of Amazonas, Brazil. For this, data were collected from confirmed cases of COVID-19 from the Fundação de Vigilância em Saúde (FVS / AM), treated by the geostatistical technique of the Weighted Distance Inverse (IDW) in the geoprocessing software QGIS 3.4. These data were analysed statistically with the flows of riverboats in the State. The trips done to access health services at different levels of complexity in the State were also mapped from the IBGE Regic survey (REGIC, 2018). The results showed the association of the diffusion and evolution of the cases of COVID-19 with river transport by mobility on line riverboats, being "entry points" for the virus and with the movement of the disease toward the western part the state. Therefore, the spread by contagion in Amazonas followed the paths of the waters, by the intercity mobility of people and goods in river transport and the rapid evolution of the increase in the number of cases in the municipalities.The overall aim of this paper was to analyze the mobility and evolution of COVID-19 in Brazilian state of the Amazonas. Diffusion axes of disease were mapped and statistically analyzed in association of rowboats flows in the state. The results described an association of diffusion and evolution of the COVID-19 cases with the fluvial transport of viruses by mobility of the rowboats flows, which contributed to the internalization of disease in the state.